2018
DOI: 10.1016/j.ygyno.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal duration of human chorionic gonadotrophin surveillance following evacuation of a molar pregnancy? A retrospective analysis on over 20,000 consecutive patients

Abstract: Our results show that pGTN can occur after hCG normalisation following PHM but the risk is extremely low. Women with CHM have a comparatively higher risk of pGTN after hCG normalisation. Those with CHM where hCG normalises within 56days have a lower risk of pGTN. We have revised the current UK hCG surveillance protocol for PHM to a single additional confirmatory normal urine hCG measurement one month after first normalisation. The protocol for CHM remains unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 4 publications
0
36
0
Order By: Relevance
“…Risk of recurrence is low (,2%) after a single molar pregnancy but increases significantly for women who experience one or more recurrences. 2,3,6,12,13,20 Once normalized, recurrent elevation of hCG has been reported in ,1% of patients. 20,21 The occurrence of GTN following hCG normalization is rare after the recommended 6 months of postnormalization hCG monitoring.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk of recurrence is low (,2%) after a single molar pregnancy but increases significantly for women who experience one or more recurrences. 2,3,6,12,13,20 Once normalized, recurrent elevation of hCG has been reported in ,1% of patients. 20,21 The occurrence of GTN following hCG normalization is rare after the recommended 6 months of postnormalization hCG monitoring.…”
Section: Treatmentmentioning
confidence: 99%
“…2,3,6,12,13,20 Once normalized, recurrent elevation of hCG has been reported in ,1% of patients. 20,21 The occurrence of GTN following hCG normalization is rare after the recommended 6 months of postnormalization hCG monitoring. 22 A recent study showed that patients with complete HM who normalized beyond 56 days after uterine evacuation had a 3.8-fold higher risk of developing postmolar GTN.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiating of a complete mole from a partial mole is particularly important for choosing sufficient length of follow-up. With partial moles the risk of subsequent GTN is several-fold lower [17]. When a partial mole in a singleton pregnancy is evacuated, the patient needs to remain under observation for 4 weeks after the normalization of hCG.…”
Section: Discussionmentioning
confidence: 99%
“…Due to lack of specific histological features, GTN is mainly diagnosed by beta-hCG surveillance. [ 3 , 4 ] Although most women can be cured by chemotherapy, many interesting issues arise. For example, we still do not fully understand why molar pregnancy happens and cannot predict whether it will recur or be followed by the development of GTN.…”
Section: Introductionmentioning
confidence: 99%